Women’s Gender Roles in Traditional Nomadic Society - Elmuratovna, Yesimova (Buletin Antropologi Indonesia, 2024)
The purpose of this study is to study the role and status of women in nomadic society, to identify the specifics of understanding the image of a woman in the traditional philosophical worldview. Attention to the study of the role of women and their image in philosophy is of constant interest, since this issue has both ideological and practical significance. In the context of the constant transformation of the structure of modern society under the pressure of various aspects, the image of a woman, her functions and role in society are undergoing changes.